People's Republic of China : Hong Kong Special Administrative Region; Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Hong Kong, like other city financial centers, has a high private saving rate. This paper seeks to understand what the principal drivers of saving and investment in financial centers are. Cyclical frequency changes affecting international financial and trade linkages are key drivers of saving and investment fluctuations in Hong Kong. Hong Kong has a long-established track-record as Asia's premier center for cross-border financial transactions. Its preeminence derives from its special link with Mainland China, with respect to foreign direct investment flows.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet